Strategy for Developing the Potential of Sanrobengi Island Tourism Object, Takalar Regency - Ayensi Mokoginta; Suparli Suparli; Tobias Mokwena (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study is to identify factors that influence the development of Sanrobengi Island Tourism Object, Takalar Regency. And to find out the strategy for developing the potential of Sanrobengi Island Tourism Object, Takalar Regency. Methodology: The analysis method used is chi-square, then a contingency test is used in drawing conclusions which is continued with a Likert Scale scoring system as a parameter to determine the magnitude of the relationship between variable X and Y. Furthermore, a strategy is developed to develop the potential of Sanrobengi Island tourism objects using the SWOT analysis method. The variables used consist of 5 (five) variables including: (1) Tourist Attractions; (2) Supporting Facilities; (3) Security and Comfort; (4) Information and Promotion; (5) Accessibility. Main Findings: Based on the results of the Chi-Square test, factors that significantly influence the development of the Potential of Sanrobengi Island Tourism Objects were obtained. There are three variables that have an influence on the strategy for developing the potential of Sanrobengi Island tourism objects in Takalar Regency, namely tourist attractions, Tourism Support Facilities, and Accessibility. While there are two variables that do not have an influence, namely Security and Comfort and Information and Promotion. Novelty/Originality of this study: This study integrates RTRW and RIPPARNAS policies to support sustainable tourism in South Sulawesi. Through the Chi-Square test, the study evaluates the attractiveness, facilities, security, promotion, and accessibility, and formulates evidence-based strategies to strengthen marine tourism as a leading destination.